Integrating Spiritual and Cognitive Dimensions: A Comparative Study of Muhammad Natsir and Jean Piaget's Character Education for the Modern Era - Euis Supianah; Sururin Sururin; Erba Rozalina Yulianti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article discusses the comparative concept of character education from two different perspectives, namely the Islamic perspective represented by the thoughts of Muhammad Natsir and the Western perspective put forward by Jean Piaget. This study aims to examine the fundamental similarities and differences in how the two figures understand and develop character education, while also examining its relevance in responding to the challenges of globalization and formulating a character education model that suits the needs of the modern era. By using the literature review method and a descriptive-comparative approach, this study reveals that Natsir places prophetic character education based on monotheism as the main foundation, which includes the dimensions of transcendence, humanization, and liberation in order to form a human being who is balanced between physical and spiritual aspects. On the other hand, Piaget emphasized the moral development of children through cognitive stages, emphasizing the importance of a socio-moral environment based on mutual respect, as well as a constructivist approach in the formation of moral understanding. The results of the study indicate a point of similarity in the attention to the formation of the whole individual and the role of learning experiences in the educational process. However, fundamental differences are seen in the philosophical basis used, namely the spiritual-religious approach of Natsir and the rational-cognitive approach of Piaget. This study concludes that the integration of these two perspectives has the potential to enrich the development of a holistic character education model that is relevant to the current context, especially in Indonesia, in an effort to shape a generation that is morally and intellectually strong.